Corn (Zea mays L.): A low methylmercury staple cereal source and an important biospheric sink of atmospheric mercury, and health risk assessment. (October 2019) - Sun, Guangyi; Feng, Xinbin; Yin, Runsheng; Zhao, Huifang; Zhang, Leiming; Sommar, Jonas; Li, Zhonggen; Zhang, Hua
Abstract: In mercury (Hg) contaminated areas of Asia, human exposure to toxic methyl-Hg (MeHg) through a rice-based diet of locally produced crop may pose a health threat. Alternative cropping system to rice in such areas would be most desirable. In this study, corn, the leading cereal source in the world with large biomass, was demonstrated to accumulate an insignificant amount of MeHg from the soil in its edible portion compared to that in rice, suggesting corn being a very competitive alternative crop. By examining Hg stable isotope composition, Hg in the aerial parts of corn was found to be mostly from the atmosphere. Maize cropping worldwide is estimated to be a discemible sink of atmospheric Hg with approximately 44 Mg Hg accumulated in each growing season on a yearly basis, most of which is from foliar uptake of atmospheric Hg and this amount is comparable to litterfall Hg observed in North America and Europe. It is thus recommended to use corn as a replacement of rice in highly Hg-contaminated areas for remediation of Hg pollution in the food supply. Graphical abstract: Unlabelled Image Highlights: Mercury in the aerial parts of corn was found to be mostly from the atmosphere. Maize cropping worldwide is estimated to be a discemible sink of atmospheric Hg. Corn was recommended to use as a replacement of rice in highly Hg-contaminated areas.